Magnetic particle translation as a surrogate measure for synovial fluid mechanics. (26th July 2017) - Shah, Yash Y.; Maldonado-Camargo, Lorena; Patel, Neal S.; Biedrzycki, Adam H.; Yarmola, Elena G.; Dobson, Jon; Rinaldi, Carlos; Allen, Kyle D.
Abstract: The mechanics of synovial fluid vary with disease progression, but are difficult to quantify quickly in a clinical setting due to small sample volumes. In this study, a novel technique to measure synovial fluid mechanics using magnetic nanoparticles is introduced. Briefly, microspheres embedded with superparamagnetic iron oxide nanoparticles, termed magnetic particles, are distributed through a 100 μL synovial fluid sample. Then, a permanent magnet inside a protective sheath is inserted into the synovial fluid sample. Magnetic particles translate toward the permanent magnet and the percentage of magnetic particles collected by the magnet in a given time can be related to synovial fluid viscosity. To validate this relationship, magnetic particle translation was demonstrated in three phases. First, magnetic particle translation was assessed in glycerol solutions with known viscosities, demonstrating that as fluid viscosity increased, magnetic particle translation decreased. Next, the relationship between magnetic particle translation and synovial fluid viscosity was assessed using bovine synovial fluid that was progressively degenerated via ultrasonication. Here, particle collection in a given amount of time increased as fluid degenerated, demonstrating that the relationship between particle collection and fluid mechanics holds in non-Newtonian synovial fluid. Finally, magnetic particle translation was used to assess differences between healthy and OA affected joints in equine synovial fluid. Here, particle collection in a given time was higher in OA joints relative to healthy horses ( p  < 0.001). Combined, these data demonstrate potential viability of magnetic particle translation in a clinical setting to evaluate synovial fluid mechanics in limited volumes of synovial fluid sample.